Pre- and post-treatment of α-Tocopherol on cognitive, synaptic plasticity, and mitochondrial disorders of the hippocampus in icv-streptozotocin-induced sporadic Alzheimer’s-like disease in male Wistar rat - Nabavi Zadeh, Fatemeh; Nazari, Maryam; Amini, Abdollah; Adeli, Soheila; Barzegar Behrooz, Amir; Fahanik Babaei, Javad (Frontiers in Neuroscience, 2023)
Introduction: Alzheimer's disease (AD), a multifaceted, progressive neurodegenerative disease, accounts for the vast majority of dementia cases in the elderly population. Streptozotocin (STZ) administered intra-cerebroventricular (ICV) in rats causes abnormal brain insulin signaling, oxidative stress, and mitochondrial dysfunction impairs cognition, ultimately altering neural plasticity and driving neuronal death. The current investigation aims to clarify the neuroprotective role of alpha-tocopherol (α-T) in improving mitochondrial function and the role of synaptic function in memory-impaired rats caused by icv-STZ. Methods: Male Wistar rats were pre-treated with (α-T 150mg/kg) orally once daily for 7 days before or 14 days after being bilaterally injected with icv-STZ (3mg/kg), while sham group rats received the same volume of STZ solvent. After 2 weeks of icv-STZ infusion, rats were tested for cognitive performance using a behaviors test and then were prepared electrophysiology recordings or sacrificed for biochemical and histopathological assays. Results: In the behavioral paradigms, those who had taken α-T had much reduced cognitive impairment. In the hippocampus of icv-STZ rat brains, α-T successfully mitigated the decline in glutathione level and superoxide dismutase enzyme activity, decreased mitochondrial ROS and mitochondrial membrane potential, and also induced a reduction in Aβ aggregation and neuronal death. Conclusion: Our results showed that α-T improved intracellular calcium homeostasis and reversed neurodegenerative abnormalities in the brain by reducing icv-STZ-mediated neurobehavioral deficits, oxidative stress, and mitochondrial dysfunction. This finding demonstrates a strategy for delating and treating AD linked to mitochondrial dysfunction and plasticity disorders.